2015
DOI: 10.1186/s12936-015-0743-y
|View full text |Cite
|
Sign up to set email alerts
|

Malaria-like symptoms associated with a natural Plasmodium reichenowi infection in a chimpanzee

Abstract: Although Plasmodium infections have never been clearly associated with symptoms in non-human primates, the question of the pathogenicity of Plasmodium parasites in non-human primates still remains unanswered. A young chimpanzee, followed before and after release to a sanctuary, in a semi-free ranging enclosure located in an equatorial forest, showed fever and strong anaemia associated with a high Plasmodium reichenowi infection, shortly after release. The animal recovered from anaemia after several months desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…P. falciparum infection of captive bonobos in the Democratic Republic of the Congo were also not associated with apparent clinical signs or increased body temperature (Krief et al, 2010). Moreover, a young chimpanzee newly transferred to a sanctuary after 6 years of captivity in an urban setting developed severe anaemia and hyperthermia concomitant with a high P. reichenowi parasitaemia (Herbert et al, 2015). The latter case would suggest that infection with certain malaria parasites can, under certain circumstances, be detrimental for chimpanzees' health.…”
Section: Pathogenicity Of Malaria Parasites In African Great Apesmentioning
confidence: 99%
See 1 more Smart Citation
“…P. falciparum infection of captive bonobos in the Democratic Republic of the Congo were also not associated with apparent clinical signs or increased body temperature (Krief et al, 2010). Moreover, a young chimpanzee newly transferred to a sanctuary after 6 years of captivity in an urban setting developed severe anaemia and hyperthermia concomitant with a high P. reichenowi parasitaemia (Herbert et al, 2015). The latter case would suggest that infection with certain malaria parasites can, under certain circumstances, be detrimental for chimpanzees' health.…”
Section: Pathogenicity Of Malaria Parasites In African Great Apesmentioning
confidence: 99%
“…Genetic regulation of the immune response by certain alleles encoding the major histocompatibility complexes I and II, several interleukins, the CD40 ligand, the nitric oxide synthase, and interferon α and γ receptors has been associated with protection against severe malaria in humans (Hill et al, 1991;Kwiatkowski, 2005). Mutations leading to variants of erythrocyte characteristics also provide protection against parasite invasion -for example, the Duffy negativity for P. vivax; glycophorin A, B and C deficiency for P. falciparum; and haemoglobin E (β-globin gene mutation) -or confer protection against clinical malaria, such as haemoglobin S (sickle haemoglobin) and C (both β-globin gene mutations), glucose-6-phosphate dehydrogenase (G6PD) deficiency and α + -thalassemia (defective production of α globin) (Kwiatkowski, 2005;Williams, 2006).…”
Section: Extrinsic and Intrinsic Determinants Of Plasmodium Infectionmentioning
confidence: 99%
“…However, studies of habituated chimpanzees in the Tai National Forest in Cote d’Ivoire revealed higher fecal parasite burdens in both young (De Nys et al, 2013) and pregnant (De Nys et al, 2014) animals, similar to what has been described in humans in malaria endemic regions. Moreover, a recent report of an initially Plasmodium naive chimpanzee, who was introduced into a sanctuary where ape Laverania infections were endemic, showed that P. reichenowi can cause high parasitemia associated with fever and anemia (Herbert et al, 2015). In contrast, other captive chimpanzees in African sanctuaries that tested positive for Laverania or P. vivax sequences in their blood or fecal samples, were asymptomatic and blood smear negative (Herbert et al, 2015; Sundararaman et al, 2016).…”
Section: Natural History Of Ape Plasmodium Infectionsmentioning
confidence: 99%
“…Moreover, a recent report of an initially Plasmodium naive chimpanzee, who was introduced into a sanctuary where ape Laverania infections were endemic, showed that P. reichenowi can cause high parasitemia associated with fever and anemia (Herbert et al, 2015). In contrast, other captive chimpanzees in African sanctuaries that tested positive for Laverania or P. vivax sequences in their blood or fecal samples, were asymptomatic and blood smear negative (Herbert et al, 2015; Sundararaman et al, 2016). Thus, it seems clear that Plasmodium infections can be pathogenic in apes; however, like humans, apes seem to develop resistance to life threatening malaria in areas of intense parasite transmission.…”
Section: Natural History Of Ape Plasmodium Infectionsmentioning
confidence: 99%
“…P. falciparum ’s closest relative is a gorilla parasite, P. praefalciparum , and its next closest relative is a chimpanzee parasite, P. reichenowi (8). Despite their high genetic similarity to P. falciparum , it is unknown whether ape parasites are as virulent in their natural hosts (53). While only limited DNA sequence data exist for P. praefalciparum , the genome of P. reichenowi has been fully sequenced (42).…”
Section: Discussionmentioning
confidence: 99%